2020
DOI: 10.1186/s13643-020-01302-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between subthreshold depression and self-care behaviors in people with type 2 diabetes: a systematic review of observational studies

Abstract: Background: Self-care behaviors in people living with type 2 diabetes are important to achieving optimal glycemic control. Major depression in type 2 diabetes is associated with decreased adherence to self-care behaviors. The association between subthreshold depression and self-care behaviors, however, has not previously been systematically reviewed. The objective of this review is to determine the association between subthreshold depression and self-care behaviors. Methods: A systematic search was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…The association between depression and OHQOL identified in the synthesized data may reflect amotivation regarding oral hygiene behaviors. Individuals with depression often decrease their engagement in daily activities, including self-care and hygiene behaviors [ 8 12 ], and a prominent characteristic of depression is amotivation [ 13 ]. However, given that studies were cross-sectional in nature, the extent to which poor OHQOL may induce depression or features of depression may promote poor OHQOL warrants additional investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between depression and OHQOL identified in the synthesized data may reflect amotivation regarding oral hygiene behaviors. Individuals with depression often decrease their engagement in daily activities, including self-care and hygiene behaviors [ 8 12 ], and a prominent characteristic of depression is amotivation [ 13 ]. However, given that studies were cross-sectional in nature, the extent to which poor OHQOL may induce depression or features of depression may promote poor OHQOL warrants additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The association between anxiety and OHQOL may also be explained by disrupted oral hygiene behaviors. Given worries, individuals with anxiety may not engage habitually in daily activities, including self-care and hygiene behaviors [ 8 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, subthreshold depression is common in people with type 2 diabetes (T2D) and may be associated with poor self‐care behaviours (Albertorio‐Diaz et al, 2017). In a systematic review, we identified two previous studies that have examined the association between subthreshold depression and self‐care behaviours in people with T2D (Shrestha et al, 2020). The results of these studies were discrepant, and important sources of bias were identified; further research to test this association is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Existen pocos estudios para determinar la naturaleza de la relación de causalidad entre depresión y adherencia al tratamiento y algunos de ellos reportan resultados inconsistentes y de baja rigurosidad a nivel metodológico (Escobedo et al, 2007;Rivas-Acuña et al, 2011). Por lo expuesto, la presente investigación tratar de evaluar cuál sería el modelo más adecuado, aquel donde la depresión infl uye negativamente a la adherencia o la adherencia al tratamiento infl uye negativamente a la depresión (Moral de la Rubia & Cerda, 2015;Shrestha et al, 2020).…”
unclassified